Cryptic frenulates are the dominant chemosymbiotrophic fauna at Arctic and high latitude Atlantic cold seeps - Sen, Arunima; Duperron, Sebastien; Hourdez, Stephane; Piquet, Berenice; Léger, Nelly; Gebruk, Andrey; Le Port, Anne-Sophie; Svenning, Mette Marianne; Andersen, Ann C. (PLOS ONE, 2018)
Source at https://doi.org/10.1371/journal.pone.0209273 . We provide the first detailed identification of Barents Sea cold seep frenulate hosts and their symbionts. Mitochondrial COI sequence analysis, in combination with detailed morphological investigations through both light and electron microscopy was used for identifying frenulate hosts, and comparing them to Oligobrachia haakonmosbiensis and Oligobrachia webbi, two morphologically similar species known from the Norwegian Sea. Specimens from sites previously assumed to host O. haakonmosbiensis were included in our molecular analysis, which allowed us to provide new insight on the debate regarding species identity of these Oligobrachia worms. Our results indicate that high Arctic seeps are inhabited by a species that though closely related to Oligobrachia haakonmosbiensis, is nonetheless distinct. We refer to this group as the Oligobrachia sp. CPL-clade, based on the colloquial names of the sites they are currently known to inhabit. Since members of the Oligobrachia sp. CPL-clade cannot be distinguished from O. haakonmosbiensis or O. webbi based on morphology, we suggest that a complex of cryptic Oligobrachia species inhabit seeps in the Norwegian Sea and the Arctic. The symbionts of the Oligobrachia sp. CPL-clade were also found to be closely related to O. haakonmosbiensis symbionts, but genetically distinct. Fluorescent in situ hybridization and transmission electron micrographs revealed extremely dense populations of bacteria within the trophosome of members of the Oligobrachia sp. CPL-clade, which is unusual for frenulates. Bacterial genes for sulfur oxidation were detected and small rod shaped bacteria (round in cross section), typical of siboglinid-associated sulfur-oxidizing bacteria, were seen on electron micrographs of trophosome bacteriocytes, suggesting that sulfide constitutes the main energy source. We hypothesize that specific, local geochemical conditions, in particular, high sulfide fluxes and concentrations could account for the unusually ...